Typology of farm households and irrigation systems: Some evidence from Nigeria - Takeshima, Hiroyuki; Edeh, Hyacinth O. (International Food Policy Research Institute, 2013)
This report summarizes the typology of farm households and irrigators in Nigeria. We apply a cluster analysis method to the Living Standard Measurement Survey (LSMS)—Integrated Survey on Agriculture data and various secondary data. We also compare the costs and inputs used across different irrigation crops, as reported in Nigeria. Findings indicate that the three major irrigation systems in Nigeria are (1) labor-intensive diverted stream irrigation of rice, (2) supplementary irrigation of coarse grains and legumes using groundwater, and (3) dry season irrigation of vegetables.